Effects of 8-week medicine ball training on physical and skill performance among basketball players - Thanuraj, Suntharalingam (2023)
Medicine ball training has been studied to determine if it can help to improve physical performance and skills performance of basketball players. This study investigated the effects of eight weeks of medicine ball training on physical performance and basketball skill performance among male basketball players aged 18 to 24 years. 28 subjects were recruited into two groups, namely the experimental group (EG) and the control group (CG), with 14 subjects in each group (EG: mean age was 21.25 ±1.34 and CG: mean age was 20.52 ±1.77). To detect differences within and between the study groups, repeated-measures ANOVA was used. The analyses demonstrated significant pre-test, mid-test and post-test effects on physical performance. All the physical performance fitness variables examined were significant with p<0.01 and the skill performance analyses showed significant differences in all variables with p<0.01. The experimental group (EG) that received medicine ball training showed improvements in physical performance, which was expressed in the form of percentage in the following variables: Overhead Medicine Ball Throw (OHMBT) (5.11%), Standing Long Jump (SLJ) (4.52%), Sprinting 20 m (SPRINT) (1.34%), Agility T-Test (AGILITY) (3.49%), Vertical Jump (VJ) (6.45%), and Back and Leg Dynamometer (BLD) (16.40%). Moreover, this study found that the experimental group that received medicine ball training showed improvement in basketball skill performance as well, which was expressed in the form of percentage in the following measures: Control Dribble (CD) (2.14%), Defensive Movement (DM) (3.22%), Passing (PASS) (6.83%), and Speed Spot Shooting (SSS) (13.29%). This research suggests that incorporating medicine ball training into regular exercise routines can significantly increase physical performance and basketball skills. Coaches are advised to include medicine ball workouts into players' daily training regimes. The incorporation of medicine ball workouts that align with specific skill work can improve basketball skill performance. The recommended medicine ball workout program provides a useful framework for evaluating improvements in physical performance and basketball skill performance among basketball players.